ANALYSISS IMPLEMENTATION OF PSAK 105 IN ACCOUNTING PRACTICE MUDHARABAH FINANCING OF INDONESIAN SHARIA BANK (BSI) LHOKSEUMAWE - Atika Salsabila Widyadhari (RADJA PUBLIKA, 2023)
This study focuses on how to apply mudharabah financing accounting based on PSAK No. 105 contained in Bank Syariah Indonesia (BSI) Lhokseumawe. The purpose of the results of this study is to find out how to apply accounting for mudharabah financing based on PSAK No. 105. The research method used is a qualitative method approach. The results of this study are that at Bank Syariah Indonesia (BSI) Lhokseumawe has implemented mudharabah financing accounting based on PSAK No. 105 so that the hope that can be reviewed is that Bank Syariah Indonesia (BSI) Lhokseumawe can improve HR performance again in terms of service and preparation of reports contained in Bank BSI Lhokseumawe in order to maintain public trust.